170 lat realizacji systemu ochrony przez wychowanie w koncepcji Edmunda Bojanowskiego - Opiela, s. Maria (Biuletyn Historii Wychowania, 2020)
The pedagogical thought and concept of the system of protection by Edmund Bojanowski’s upbringing, even though it was born 170 years ago, appears today to be innovative and exceptionally up-to-date. Applied in contemporary pre-school education and child care, it is a continuation of the concept of upbringing and its practical implementation by establishing on May 3, 1850 the nursery and Congregation of the Servant Sisters. The theoretical and practical application of this concept and new research and scientific studies on the essence of early education realized in Catholic pedagogical thought in the context of contemporary civilization challenges is still expected from various circles in Poland and worldwide.